Experimental modal analysis of masonry arches strengthened with graphene nanoplatelets reinforced prepreg composites - Cakir, Ferit; Uysal, Habib; Acar, Volkan (ELSEVIER SCI LTD, 2016)
Strengthening of masonry structures with different engineering materials has become a challenge for civil engineers with the advancements in engineering technology. This study mainly focused on dynamic parameters of masonry arches, which were strengthened with nanoparticle reinforced prepreg composites. For this purpose, the prepreg composites were produced with carbon fiber and epoxy system which was reinforced with graphene nanoplatelets particles that was 1 wt% of the epoxy system. Afterwards, four different strengthening alternatives were performed at the extrados and intrados of the masonry arches. Finally, dynamic characteristics such as mode shapes and modal frequencies of unstrengthened and strengthened arches were determined through experimental modal analysis (EMA) and numerical analysis. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Prepreg composites; Graphene nanoplatelets; Brick masonry arches; Experimental modal analysis (EMA); Finite element analysis (FEA); CARBON-FIBER; PERFORMANCE; Engineering; Instruments & Instrumentation